Improving Student Learning Outcomes Through the Think Pair and Share Model in Chemistry Learning - Srinadi, Ni Putu (Universitas Negeri Makassar, 2023)
Think Pair and Share learning is a way of learning designed for students so they can be pushed into the flow of interaction and communication. Think Pair and Share was first developed by Frank Lyman and his colleagues at the University of Maryland in 1985. Therefore, it aims to find out whether the Think Pair and Share model can improve learning outcomes in Chemistry class XI MIPA 1 SMAN 1 Sigi even semester of the 2022 academic year/ 2023 and to find out how to describe the application of the Think Pair and Share model so that it can improve learning outcomes in Chemistry class XI MIPA 1 SMAN 1 Sigi even semester of the 2022/2023 academic year. This study used classroom action research with research subjects being class XI MIPA 1 students with a total of 27 people consisting of 6 men and 21 women with data collection techniques, namely qualitative data and quantitative data. The results of this study indicate that the Think Pair and Share Model can improve learning outcomes in Chemistry class XI MIPA 1 SMAN 1 Sigi even semester of the 2022/2023 academic year because the highest score in cycle I is 100 as many as 1 person in cycle II the highest score increases to 100 as many as 4 people. The lowest score in cycle I was 50 for 2 people and in cycle II the lowest score was only 1 person who was worth 50